Operating point of Capacitive Micromachined Ultrasonic Transducers with Sub-structural Elements - Morkvenaite-Vilkonciene, I.; Virzonis, D.; Vanagas, G.; Krikscikas, V. (Elektronika ir Elektrotechnika, 2012)
CMUT FEM 2D electrostatic model was created to investigate dielectric surface roughness influence to the operating point. Three different form structures: triangle, half-circle, rectangle were investigated. The highest electric field norm concentration on the triangle apex was found. For experiments, dielectric surface was etched by two etching steps to define the cavity: reactive ion etching and buffered oxide etching for smoothing the cavity bottom. Atomic force microscopy was used to monitor and control the roughness of the cavity bottom. The simulation showed the decrease of the effective gap by 0.6 % and 1.0 % in 10 and 20 nm RMS cases, respectively. Voltage-capacitance tests of the fabricated devices with known roughness values confirmed the assumptions about the roughness-induced operating point shifts. DOI: http://dx.doi.org/10.5755/j01.eee.18.9.2804